Meiotic Recombination Defects and Premature Ovarian Insufficiency - Huang, Chengzi; Guo, Ting; Qin, Yingying (Frontiers in Cell and Developmental Biology, 2021)
Premature ovarian insufficiency (POI) is the depletion of ovarian function before 40 years of age due to insufficient oocyte formation or accelerated follicle atresia. Approximately 1%-5% of women below 40 years old are affected by POI. The etiology of POI is heterogenous, including genetic disorders, autoimmune diseases and iatrogenic factors. Genetic factors account for 20-25% of patients. However, more than half of the patients were idiopathic. With the widespread application of next-generation sequencing, the genetic spectrum of POI has been expanded, especially the latest identification in meiosis and DNA repair related genes. During meiotic prophase I, the key processes include DNA double-strand breaks (DSBs) formation and subsequent homologous recombination (HR), which are essential for chromosome segregation at the first meiotic division and genome diversity of oocytes. Many animal models with defective meiotic recombination present with meiotic arrest, DSBs accumulation and oocytes apoptosis, which are similar to human POI phenotype. In the article, based on different stages of meiotic recombination, including DSBs formation, single strand invasion and recombination, crossover formation and resolution, we reviewed the individual gene mutations identified in POI patients and the potential candidate genes for POI pathogenesis, which will shed new light on the genetic architecture of POI and facilitate risk prediction, ovarian protection, and early intervention for POI women.